A carnavalização em ópera do malandro: diálogos (inter)semióticos - Lima , Rafael Torres Correia (2017)
This work intends to analyze the play Ópera do Malandro written by Chico Buarque, concomitantly to the homonymous film directed by Ruy Guerra, using as theorical basis the Semiotic of Culture of Russian orientation together with the concept of carnavalization in order to modelize the image of the lazy stock character, present in both semiotic languages. The main objectives of this research are: to analyze the multiple aspects of carnavalization present in both the play and the film; to resignify the figure of the lazy stock character according to the other character’s point of view and finally, to verify in which way the lazy stock character image is performed and deconstruct through the songs which constitute the dramatic text. This research will be mainly supported by the theories of the carnavalization and the serious-comic gender, postulated by Mikhail Bakhtin. The analyze of the comic in the focused objects will be based on the ideas of Propp and Bergson. The discussion related to the Semiotic of Culture will be sustained by Lótman and Machado. Erika Fisher-Lichtie, Veltruski and Kowzan provided the basis to the studies related to the semiotics of the theatre. Based on the ideas of all these theorists, we intend to decodify and to resignify the process of carnavalization occurred in these two distinct semiotic languages, using the representation of the lazy stock character as the mediator linking between then.